THE ACADEMIC DISCIPLINE OF SOCIAL WORK AND SCIENTIFIC JOURNAL - DUNAJEVAS, Eugenijus (Socialinė teorija, empirija, politika ir praktika, 2016)
The goal of the paper was to explore the development of social work academic discipline through the lenses of scientific journal STEPP. The relationship between academic discipline and scientific journal is explained in the first part of the paper. Wallerstein’s theory of academic discipline and Ostrom’s framework for institutional analysis and development were employed in order to justify the relationship between academic discipline and scientific journal. The value of discipline correlates with the value of journal. The methods for journals value measurement are discussed in the second part of the paper. It can be defined by two types of journal value measurement tools. The content of journal is measured through the citing in the first method. The indicators of various journal characteristics are measured with the second tool. The value of journal STEPP was analysed in the third part of the paper. It was taken that the dynamics of journal’s value express the dynamics of value of social work discipline at Vilnius University. The second type of journal value measurement tool was employed. Such indicators as periodicity and the quality of content suggest the rise of journal’s value. The indicator of specificity shows that the journal is dominated by two disciplines – social work and social policy. On the other hand, it is not possible to specify the trend of journal’s value change, according to the indicator of specificity. Overall, the results of data analyses suggest the rise of journal and discipline value.